(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de Rex Winsbury, The Roman Book. Books, Publishing and Performace in Classical Rome, London, Duckworth Classical Literature and Society, 2009, 236 pp. ISBN 978-0-71-563829-3